Direct Copper-Free Domino Conjugate Addition-Cycloallylation using Organozinc Reagents - Komanduri, Venukrishnan (2008)
The Direct Approach: Enones possessing appendant allylic carbonates react directly with diorganozinc reagents in the presence of zinc diiodide [ZnI(2)] to provide 5- and 6-membered ring products of tandem or domino conjugate addition-cycloallylation in good to excellent yield. In a related copper-free transformation, allylic carbonates are found to engage in direct allylic substitution with diorganozinc reagents.